The quiet revolution in staple food value chains: Enter the dragon, the elephant, and the tiger - Reardon, Thomas; Chen, Kevin Z.; Minten, Bart; Adriano, Lourdes (Asian Development Bank, 2012)
Feeding nine billion people by 2050 is a top priority on the global agenda for sustainable and inclusive development. This task is especially formidable in Asia, where more than two-thirds of the world’s poor and malnourished people live. Food prices in Asia are projected to remain high and volatile, and food production is likely to be challenged by the combined effects of resource degradation and increasing climate variability and change. Ensuring food security in this region requires urgent actions to improve the productivity and climate resilience of agriculture and to upgrade the food value chains to ensure adequate and affordable food supplies.